Hubungan Berat Badan Lahir dan Pemeriksaan ANC dengan Stunting pada Anak Umur 0-59 Bulan - Harauly Lady Lusiana Manalu; Nur Anisah; Riana Sihotang; Misliani Misliani; Nurainun Hasibuan; Mira Lisda (Malahayati Nursing Journal, 2024)
ABSTRACT Stunting is a major threat to the quality of Indonesian people, as well as a threat to the nation's competitiveness. This is because being stunted, not only disrupts physical growth (short stature), but also disrupts brain development, which of course will greatly affect ability and achievement at school, as well as productivity and creativity at productive ages (Ministry of Health, 2018) . The aim of this study was to determine whether there was a relationship between birth weight and ANC examination and stunting in children aged 0-59 months. The design used in this study was cross-sectional to see whether there was a relationship between birth weight and ANC examinations with stunting in children aged 0-59 months in the past. The population in this study was 50 children aged 0-59 months at the Sally Clinic in Medan. The sample for this research was 50 children aged 0-59 months at the Sally Clinic in Medan. The sampling technique uses saturated sampling or total sampling. Analysis of research data is univariate and bivariate analysis. The results of the study explained that based on the Fisher's exact test, it was found that there was a relationship between birth weight and ANC examination with stunting in children aged 0-59 months at the Sally Clinic in Medan. The conclusion of the research is that there is a relationship between birth weight and ANC examination with Stunting in children aged 0-59 months at the Sally Clinic Medan. Keywords: Weight, ANC, Stunting, Children Aged 0-59 Months  ABSTRAK Stunting merupakan ancaman utama terhadap kualitas manusia Indonesia, juga ancaman terhadap kemampuan daya saing bangsa. Hal ini dikarenakan stunted, bukan hanya terganggu pertumbuhan fisiknya (bertubuh pendek/kerdil) saja, melainkan juga terganggu perkembangan otaknya, yang mana tentu akan sangat mempengaruh kemampuan dan prestasi di sekolah, juga produktivitas dan kreativitas di usia-usia produktif (DepKes, 2018). Tujuan penelitian ini adalah untuk mengetahui apakah ada hubungan antara berat badan lahir dan pemeriksaan ANC dengan Stunting pada anak umur 0-59 bulan. Desain yang digunakan dalam penelitian ini adalah cross-sectional untuk melihat ada hubungan antara berat badan lahir dan pemeriksaan ANC dengan Stunting pada anak umur 0-59 bulan pada masa yang telah berlalu. Populasi dalam penelitian ini adalah anak umur 0-59 bulan di Klinik Sally Medan sebanyak 50 orang. Sampel penelitian ini adalah anak umur 0-59 bulan di Klinik Sally Medan sebanyak 50 orang. Tehnik pengambilan sampel menggunakan sampling jenu atau total sampling. Analisa data penelitian adalah anlias univariat dan bivariat. Hasil penelitian menjelaskan bahwa berdasarkan uji fisher’s exact di dapatkan bahwa ada hubungan antara berat badan lahir dan pemeriksaan ANC dengan Stunting pada anak umur 0-59 bulan di Klinik Sally Medan. Kesimpulan penelitian adalah ada ada hubungan antara berat badan lahir dan pemeriksaan ANC dengan Stunting pada anak umur 0-59 bulan di Klinik Sally Medan. Kata Kunci: Berat Badan, ANC, Bayi Usia 0-58 Bulan